Meteorite impact craters and ejecta in South America: a brief review - Acevedo, Rogelio Daniel (2011)
The first catalogue of impact craters sites in South America is presented here. Proximately thirty proven, suspected and disproven structures have been identified by several sources in this continent until now. But everyone events proposed here aren´t really produced by impacts at all. About some of them reasonable doubts exist. Argentina and Brazil are leading the list containing almost everything detected. In Bolivia, Perú, Chile, Colombia and Uruguay only a few were observed. The rest of countries are awaiting for new discoveries.